Lineage Relationships Between Subpallial Progenitors and Glial Cells in the Piriform Cortex - Sánchez-González, Rebeca; López-Mascaraque, Laura (Frontiers in Neuroscience, 2022)
The Piriform cortex is a paleocortical area, located in the ventrolateral surface of the rodent forebrain, receiving direct input from the olfactory bulb. The three layers of the PC are defined by the diversity of glial and neuronal cells, marker expression, connections and functions. However, the glial layering, ontogeny and sibling cell relationship along the PC is an unresolved question in the field. Here, using multi-color genetic lineage tracing approaches with different StarTrack strategies, we performed a rigorous analysis of the derived cell progenies from progenitors located at the subpallium ventricular surface. First, we specifically targeted E12-progenitors with UbC-StarTrack to analyze their adult derived-cell progeny and their location within the piriform cortex layers. The vast majority of the cell progeny derived from targeted progenitors were identified as neurons, but also astrocytes and NG2-cells. Further, to specifically target single Gsx-2 subpallial progenitors and their derived cell-progeny in the piriform cortex, we used the UbC-(Gsx-2-hyPB)-StarTrack, to perform an accurate analysis of their clonal relationships. Our results quantitatively delineate the adult clonal cell pattern from single subpallial E12-progenitors, focused on glial cells. In summary, there is a temporal pattern in the assembly of the glial cell diversity in the piriform cortex, that also reveals a spatio-temporal progenitor heterogeneity.